The name of the rose [videorecording (DVD)] - Birkin, Andrew; Brach, Gérard; Franklin, Howard; Godard, Alain (Screenwriter); Connery, Sean; Abraham, F. Murray; Baskin, Elya; Eco, Umberto (Samuel Goldwyn Films, 2024)
An intellectually nonconformist friar investigates a series of mysterious deaths in an isolated abbey.